1992
DOI: 10.1002/j.2333-8504.1992.tb01467.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Borrowing and Participation in Postsecondary Education

Abstract: High school seniors who answered that they would choose to borrow, when asked what they would do if college costs were $1,500 more than they, their family, and a scholarship could provide, were significantly more likely to attend college in the next four years than were students who answered that they would choose other options (delaying college entrance, attending a less expensive college, or getting a job). This held true even after controlling for other variables such as educational aspirations, tested achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Students with less information about cost and aid are also less likely to be willing to take out loans to pay for college, or have parents that save for college (Ekstrom, 1991;Flint, 1997). The research does not establish causality though, and thus does not establish whether having knowledge causes a student to take steps to enroll in college (Perna, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Students with less information about cost and aid are also less likely to be willing to take out loans to pay for college, or have parents that save for college (Ekstrom, 1991;Flint, 1997). The research does not establish causality though, and thus does not establish whether having knowledge causes a student to take steps to enroll in college (Perna, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…That leads them to borrow cash from their friends. Some teachers even apply for parttime work to earn extra money (Ekstrom, 2014). However, the retirees say the opposite.…”
mentioning
confidence: 99%
“…These descriptive data are particularly problematic given that willingness to borrow is positively related to college enrollment (Callender & Jackson, 2005;Ekstrom, 1991). Using data from the High School and Beyond longitudinal survey of 1980 high school sophomores and seniors, Ekstrom found that students who reported that they would be willing to borrow to pay $1,500 in college prices that could not be covered by family or other sources of financial aid were more likely than other students to enroll in college within four years of graduating from high school, enroll in a four-year than a two-year institution, and enroll full-time than part-time even after controlling for background characteristics, educational aspirations, academic achievement, encouragement from significant others, and knowledge of college costs and financial aid.…”
mentioning
confidence: 99%